2022
DOI: 10.3389/fimmu.2022.1057892
|View full text |Cite
|
Sign up to set email alerts
|

Phage therapy for Clostridioides difficile infection

Abstract: Clostridioides difficile is endemic in the intestinal tract of healthy people. However, it is responsible for many healthcare-associated infections, such as nosocomial diarrhea following antibiotic treatment. Importantly, there have been cases of unsuccessful treatment and relapse related to the emergence of highly virulent strains of C. difficile and resistance to antimicrobial agents. Fecal microbiota transplantation (FMT) is considered an effective therapy for recurrent C. difficile infection. However, its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Besides above-mentioned suggestions for future FFT studies, future research should focus on targeting specific bacteria with phages to get a better mechanistic understanding of how bacterial communities are changed upon phage predation and how these changes could affect disease phenotypes. One example of specific phages targeting pathogenic bacteria is the phage cocktail developed to treat recurrent Clostridioides difficile infections 51 . Another interesting target are the Lactobacillaceae that are thought to produce ethanol and thereby contribute to non-alcoholic fatty liver disease (NAFLD) 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides above-mentioned suggestions for future FFT studies, future research should focus on targeting specific bacteria with phages to get a better mechanistic understanding of how bacterial communities are changed upon phage predation and how these changes could affect disease phenotypes. One example of specific phages targeting pathogenic bacteria is the phage cocktail developed to treat recurrent Clostridioides difficile infections 51 . Another interesting target are the Lactobacillaceae that are thought to produce ethanol and thereby contribute to non-alcoholic fatty liver disease (NAFLD) 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Bacteriophage viruses (“phages”) were first proposed in the early 20th century, prior to the discovery of antibiotics, as a means of controlling or eliminating infectious bacteria [ 89 , 90 ]. After falling out of favor with the advent of antibiotics, phage therapy is experiencing a renaissance in the treatment of antibiotic-resistant bacterial infections [ 91 ], and now in the field of microbiome therapeutics [ 89 , 91 , 92 ].…”
Section: Targeted Microbiome Therapeutics: Opportunities and Challengesmentioning
confidence: 99%
“…Phages are highly species- and often strain-specific viruses that rapidly replicate within, and then destroy target bacterial cells [ 91 , 92 , 93 ]. Phages endogenous to gut microbiomes are increasingly recognized as important dynamic factors in overall microbiome composition and function; indeed, it has been suggested that some of the microbiome composition changes seen in IBD, for example, are driven at least in part by “blooms” of endogenous phages [ 92 ].…”
Section: Targeted Microbiome Therapeutics: Opportunities and Challengesmentioning
confidence: 99%
“…Therefore, there is an urgent need to develop alternative therapeutic strategies to combat these pathogens. Bacteriophages (phages) and their derivative endolysins have emerged as promising candidates in this endeavor (Fujimoto and Uematsu, 2022; Khan and Joshi, 2022; Kortright et al, 2019; Mondal et al, 2021, 2020; Sekiya et al, 2022; Ul Haq et al, 2012). Endolysins, hydrolytic enzymes produced by phages, demonstrate a broad host spectrum and possess the advantages of rapid bacterial cell lysis, low risk of resistance development, and efficacy against biofilms and mucosal surfaces (Abdelrahman et al, 2021; Borysowski et al, 2006; Gondil et al, 2020; Heselpoth et al, 2021; Mirski et al, 2019; Nelson et al, 2012; Schmelcher et al, 2012; Schmelcher and Loessner, 2016).…”
Section: Introductionmentioning
confidence: 99%